KEMAMPUAN KONEKSI MATEMATIS SIAPA YANG LEBIH TINGGI: GURU KELAS VERSUS GURU MATA PELAJARAN? - Ari Wibowo; Hardi Hardi (AdMathEdu : Jurnal Ilmiah Pendidikan Matematika, Ilmu Matematika dan Matematika Terapan, 2021)
One learning approach that can be chosen by teachers who teach mathematics in upper class (class IV, V, VI) is by correlating or connecting mathematics. Mathematics connection is correlation among mathematics topics, correlation among mathematics and other sciences, and correlation between mathematics and real life or daily life. In this research, it is studied mathematics connection ability of upper class teachers on aljabar topic that is measured by contextual questions and factors influencing them. The population in this research is Islamic Elementary School teachers in Surakarta residency, either state or private, who teach mathematics in upper class. Meanwhile, the sample, 65, is taken randomly from the population by using cluster sample collection technique. The statistics analysis technique used is descriptive and explorative statistics and ordinal logistic regression analysis. In mathematics connection ability with other sciences, almost half (43.6 %) class teachers can answer at the highest level (complete answer). It is more than the number of subject matter teacher that is less than one-fifth (17.4 %). Explanatory variable which is included in this model is teacher status variable (class teacher and subject matter teacher). It doesnt influence significantly to teacher level in inter topic mathematics connection ability question and in mathematics connection ability question with real life or daily life. However, explanatory variable of teacher status influences significantly to teacher answer level in mathematics connection ability question with other sciences. Based on the result of ordinal logistic regression analysis, the estimated odds is 0.275. The estimated odds that class teachers answer is in low level answer, that is 0.275 times the estimated odds for subject matter teachers answer. So, class teachers answer in low level is less than subject matter teachers answer. Next, based on confidence interval 95 % of odds ratio value, it can be explained that class teacher has less probability (0.103-0.734 times), than subject matter teacher to answer in low level, in questions measuring mathematics connection ability with other sciences.